Grid Voltage Sensorless Model Predictive Control for a Single-Phase T-Type Rectifier With an Active Power Decoupling Circuit - Sertac Bayhan (16388511) (2021)
This paper proposes grid voltage sensorless model predictive control for a single-phase T-type rectifier with an active power decoupling circuit. The proposed sensorless technique is based on a model reference adaptive system (MRAS) and tested under distorted grid conditions. This study also examines the relationship among the ripple energy, the dc-link capacitor, and the active power decoupling circuit capacitor. The developed control technique is proposed to ensure the following objectives; (1) sensorless grid voltage estimation; (2) the second-order ripple power elimination; (3) reference current generation based on power equilibrium; (4) ensuring unity power factor under all operating conditions; and (5) capacitor voltage balance. The developed control structure offers simplicity and it is cost-effective due to the absence of a grid voltage sensor. An experimental prototype is established, and the main results, including the steady-state and dynamic performances, are presented to validate the effectiveness of the proposed control. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2021.3054773